Advances in developmental policy studies / edited by Stuart S. Nagel - "Nagel, Stuart S (ed.)" (London, 1996)
This first volume in the series examines such topics as improving public policy toward and within developing nations, economic development and decentralized government, policy evaluation methods for developing country energy issues, and the law of developing nations and super-optimum solutions.
Keywords: Policy sciences